2016
DOI: 10.1103/physreva.94.033815
|View full text |Cite
|
Sign up to set email alerts
|

Depolarization shift of the superradiant phase transition

Abstract: We investigate the possibility of a Dicke-type superradiant phase transition of an atomic gas with an extended model which takes into account the short-range depolarizing interactions between atoms approaching each other as close as the atomic size scale, which interaction appears in a regularized electric-dipole picture of the QED of atoms. By using a mean field model, we find that a critical density does indeed exist, though the atom-atom contact interaction shifts it to a higher value than it can be obtaine… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 27 publications
(50 reference statements)
0
51
0
Order By: Relevance
“…By considering a full description of a realistic system of atoms in a real cavity, refs. [35][36][37][38][39] showed that a phase transition can occur in the right geometry. Since the "photon creation" operator describes different physical fields in different gauges, it is important to check what physical fields acquire macroscopic expectations in such a transition.…”
Section: Other Realizations Of the Dicke Modelmentioning
confidence: 99%
“…By considering a full description of a realistic system of atoms in a real cavity, refs. [35][36][37][38][39] showed that a phase transition can occur in the right geometry. Since the "photon creation" operator describes different physical fields in different gauges, it is important to check what physical fields acquire macroscopic expectations in such a transition.…”
Section: Other Realizations Of the Dicke Modelmentioning
confidence: 99%
“…As indicated in the main text, we perform the HolsteinPrimakoff transformation, as well as the transformation (12)(13)(14), and we consider the case β = 0:b = β +d =d. This gives us for the Hamiltonian:…”
Section: Appendix A: Linear Term Expansion Of the Hamiltonianmentioning
confidence: 99%
“…In the limit of a large number of qubits, the DM undergoes a SPT [5] in the ultrastrong coupling (USC) regime, where the collective light-matter coupling becomes comparable to the qubit and field bare frequencies [6]. Although the DM is commonly used to describe atomic and solid-state systems, whether it provides a reliable description of the system ground state when approaching the critical coupling is still the subject of debate [7][8][9][10][11][12][13]. In particular, the presence of the so-called diamagnatic term is expected to prevent the SPT.…”
Section: Introductionmentioning
confidence: 99%
“…(2) [21,22]. Counter examples against that no-go theorem are still being discussed even in the cur-rent literature [23,24]. However, the thermal SRPT has not yet been realized experimentally, while its nonequilibrium analogue has been demonstrated in cold atoms [25], and a thermal-equilibrium analogue has been theoretically proposed in an artificial system composed of a superconducting circuit [26].…”
Section: (A) (B)mentioning
confidence: 99%
“…While the presence of a thermal SRPT in the minimal-coupling Hamiltonian (derived from the Maxwell equations and Newton's equation of charged particles feeling the Lorentz force) in Eq. (2) is still under debate [21][22][23][24], there remains a possibility for realizing a thermal SRPT in systems where spins, instead of charges, interact with the EM fields, as pointed out by Knight et al in 1978 [31]. A hint of such a possibility lies in certain magnetic phase transitions, which are caused by interactions between two species of spins within the same material.…”
Section: (A) (B)mentioning
confidence: 99%